2008
DOI: 10.1029/2007pa001466
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient regime at the siliceous belt of the Atlantic sector of the Southern Ocean during the past 660 ka

Abstract: [1] Sediment cores from Ocean Drilling Program sites 1094 and 1093 hold the most extensive and most detailed records of carbon and nitrogen isotopes of diatom-bound organic matter in the Atlantic sector of the Southern Ocean over the past 660 ka. These records were combined with summer sea surface temperatures and winter sea ice that were deduced from diatom transfer functions to reconstruct the nutrient regime at the northern and southern boundaries of the siliceous belt at latitudes 53°S and 50°S, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 68 publications
(125 reference statements)
3
33
0
Order By: Relevance
“…As the input of terrestrial organic matter to the open oceans is low, productivity plays a large role in determining the isotopic signature of oceanic DIC which then contributes to δ 13 C diatom . This supports the interpretation of δ 13 C diatom values from Southern Ocean cores as representing changes in productivity, where low δ 13 C diatom during the Last Glacial Maximum is thought to suggest an increase in the availability of 12 C due to low phytoplankton productivity [21,35] .…”
Section: Prospects For the Application Of δ 13 C Diatom In Lakes And supporting
confidence: 84%
See 2 more Smart Citations
“…As the input of terrestrial organic matter to the open oceans is low, productivity plays a large role in determining the isotopic signature of oceanic DIC which then contributes to δ 13 C diatom . This supports the interpretation of δ 13 C diatom values from Southern Ocean cores as representing changes in productivity, where low δ 13 C diatom during the Last Glacial Maximum is thought to suggest an increase in the availability of 12 C due to low phytoplankton productivity [21,35] .…”
Section: Prospects For the Application Of δ 13 C Diatom In Lakes And supporting
confidence: 84%
“…Comparison of δ 13 C diatom values measured in sediments from Lake Challa, Simba Tarn and Small Hall Tarn [23] with studies from ocean sediments [20][21][22] and contemporary diatoms from the English Lake District (Barker, unpublished data).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…For example, assuming the atmosphere and surface water are in equilibrium, calculated that 3‰ and 1‰ of the measured 4‰ difference in δ 13 C diatom between the last glacial and modern day are attributable to changes in productivity and pCO 2 respectively. Similarly, results in Crosta et al (2005) and Schneider-Mor et al (2005; detail change in δ 13 C diatom in the Southern Ocean over the last 640 ka also related to changes in productivity, nutrient availability and pCO 2 concentrations.…”
Section: /28mentioning
confidence: 74%
“…Crosta et al, 2005;Schneider-Mor et al, 2005 where changes in δ 15 N diatom have been shown to be anti-correlated with those in δ 30 Si diatom . The increased usage of nitrate documented in these studies during glacial periods has been used to provide further support for the silicic acid leakage hypothesis (see Section 2.2).…”
Section: Nitrogen Isotopesmentioning
confidence: 99%